Imported Malaria in Portugal 2000–2009: A Role for Hospital Statistics for Better Estimates and Surveillance. (7th December 2014) - Fonseca, Ana Glória; Dias, Sara S.; Baptista, João Luis; Torgal, Jorge
Abstract : Background . Although eradicated in Portugal, malaria keeps taking its toll on travelers and migrants from endemic countries. Disease notification is mandatory but is compromised by underreporting. Methods . A retrospective study on malaria hospitalizations for 10 consecutive years (2000–2009) was conducted. Data on hospitalizations and notifications were obtained from Central Administration of Health System and Health Protection Agency, respectively. For data selection ICD-9 CM and ICD-10 were used: codes 084 *, 647.4, and B50–B54. Variables were gender, age, agent and origin of infection, length of stay (LOS), lethality, and comorbidities. Analysis included description, hypothesis testing, and regression. Results . There were 2003 malaria hospitalizations and 480 notified hospitalized cases, mainly in young male adults. P. falciparum was the main agent of infection acquired mainly in sub-Saharan Africa. Lethality was 1.95% and mean LOS was 8.09 days. Older age entailed longer LOS and increased lethality. Discussion . From 2000 to 2009, there were 2003 malaria hospitalizations with decreasing annual incidence, these numbers being remarkably higher than those notified. The national database of diagnosis related groups, reflecting hospitalizations on NHS hospitals, may be an unexplored complementary source for better estimates on imported malaria.